Colorectal Choriocarcinoma in a Patient with Probable Lynch Syndrome - Koelzer, Viktor H.; Steuer, Karl; Gross, Ulrike Camenisch; Zimmermann, Dieter; Paasinen-Sohns, Aino; Mertz, Kirsten D.; Cathomas, Gieri (Frontiers in Oncology, 2016)
Background: Personalized therapy of colorectal cancer (CRC) is influenced by morphological, molecular and host-related factors. Here we report the comprehensive clinicopathological and molecular analysis of a pure extra-gestational colorectal choriocarcinoma in a patient with probable Lynch syndrome. Case presentation: A 61 year old female with history of gastric cancer at age 36 presented with a transmurally invasive tumor of the right hemicolon and liver metastasis. A right hemicolectomy was performed. Histopathological analysis showed a mixed trophoblastic and syncytiotrophoblastic differentiation, consistent with choriocarcinoma. Disease progression was rapid under oxaliplatin, capecitabine, irinotecan (XELOXIRI) and bevacizumab. Molecular phenotyping identified loss of the mismatch-repair (MMR) protein PMS2, microsatellite instability, a lack of MLH1 promoter methylation and lack of of BRAF mutation suggestive of Lynch-Syndrome. Targeted next generation sequencing revealed an Ataxia Telangiectasia Mutated (ATM p.P604S) missense mutation. A bleomycin, etoposide and cisplatin (BEP) treatment protocol targeting germ-cell neoplasia lead to disease remission and prolonged survival of 34 months. Conclusions: Comprehensive immunohistochemical and genetic testing is essential to identify uncommon cancers possibly related to Lynch syndrome. For rare tumors, personalized therapeutic approaches should take both molecular and morphological information into account. Key words: Colorectal cancer, choriocarcinoma, histopathology, prognostic factors, Lynch syndrome, microsatellite instability, ataxia telangiectasia mutated, molecular pathology, next generation sequencing, personalized medicine